SOLVATOCHROMIC AND SUBSTITUENT EFFECT ON ELECTRONIC ABSORPTION OF ARENETRICARBONYLCHROMIUM(0) COMPLEXES - Agus Abhi Purwoko (Indonesian Journal of Chemistry, 2008)
A number of arenetricarbonylchromium(0) complexes, [(η6-arene)Cr(CO)3], in which arene = benzene, chlorobenzene, phenyltrimethylsilane, and acenaphthene were synthesized. Electronic absorptions of these complexes were recorded in various solvents, ranging from polar to non polar ones; i.e. methanol, methylene chloride, chloroform, benzene, and isooctane. These chromium tricarbonyl complexes show lowest electronic absorption in the energy range of 313 - 320 nm, with relatively high intensity (ε = 0,9 - 2,0 x 104 M-1cm-1). Detailed discussion of the solvent and substituent effect on electronic absorption of these complexes are presented in this article.